Pengaruh Sumber Bonggol dan Media Tanam pada Pembibitan Tanaman Pisang Kayu (Musa paradisiaca L.cv.Kayu) - SUPRIANA, I KOMANG AGUS; WIJANA, GEDE; RAKA, I GUSTI NGURAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.4, No.2, April 2015, 2015)
ABSTRACT Influence of excrescence type and planting media on the seeding of banana Kayu plant ( Musa paradisiaca L . cv This research aims to obtain the treatment interaction of the best excrescence type and planting media on the seeding of banana Kayu plant. The research was conducted on April until July 2014, using Random Design Factorial Group with 3 repetitions. The first factor is the type of excrescence (sword seedling excrescence, mature seedling excrescence, and fruitful excrescence), meanwhile the second factor is the planting media of soil + sand + charcoal chaff (v:v:v = 2:1:1); soil + sand + compost (2:1:1); soil + sand + charcoal chaff + compost (2:1:0.5:0.5). Banana excrescence was taken from the healthy plant, then it was split and soaked in the Biota L solution for 1 hour. The excrescence is planted on polybag with planting media according to the treatment, and located under the shelter of paranet 75%. The result of research showed that (1) There was an interaction between the treatment of excrescence type and planting media toward the period of bud emergence, the fastest (6.6 Day after Planting) was showed in the treatment combination of mature seedling excrescence which being planted on the media of soil + sand + compost (2:1:1); (2) The use of sword seedling excrescence resulted in the height of bud, trunk circumference, amount of leaves, and the best leaf area; (3) The planting media of soil + sand + charcoal chaff (2:1:1) resulted in the height of bud, trunk circumference, amount of leaves, and the best leaf area. Keywords: Seedling of Banana Kayu, Banana excrescence, Planting media.